Diagnosis and Rehabilitation pediatrics femur Fracture by Radiography and Physiotherapy - salh, Mona A; Souliman, Sana I.; soliman, abeer A. (Aljameai, 2024)
Abstract: Femur fractures in children are a common injury that can result from accidents or trauma. The femur is the largest bone in the body and a fracture of this bone can be serious. Children are more prone to hip fractures because their bones are still growing and are not as strong as those of adults. In this study, a femur fracture was found in an 8-year-old girl at Tobruk Medical Center. Then the diagnosis was made by radiotherapy (X-rays, magnetic resonance imaging, and computed tomography). The operation was performed under radiography by (C-arm fluoroscopy), where the fracture was fixed with a plate. Finally, after the fracture healed, the patient was rehabilitated by physiotherapy to recover in the least time and return to normal daily activity. The role of physiotherapy is important for daily resumption of activity and full recovery in a short time after the fracture. More studies are needed to confirm these results. المستخلص: تعتبر كسور الفخذ عند الأطفال من الإصابات الشائعة التي يمكن أن تنتج عن الحوادث أو الصدمات. عظم الفخذ هو أكبر عظمة في الجسم ويمكن أن يكون كسر هذا العظم خطيرًا. الأطفال أكثر عرضة لكسور عظام الفخذ لأن عظامهم لا تزال تنمو وليست قوية مثل عظام البالغين. في هذه الدراسة ، تم العثور على كسر في عظم الفخذ لدى فتاة تبلغ من العمر 8 سنوات في مركز طبرق الطبي. تم التشخيص عن طريق العلاج الإشعاعي (الأشعة السينية ، التصوير بالرنين المغناطيسي ، التصوير المقطعي المحوسب)اجريت العملية تحت التصوير الشعاعي بواسطة (C-arm fluoroscopy) حيث تم تثبيت الكسر بصفيحة معدنية. أخيرًا بعد التئام الكسر ، تم إعادة تأهيل المريض عن طريق العلاج الطبيعي للتعافي في أقل وقت والعودة إلى النشاط اليومي الطبيعي. دور العلاج الطبيعي مهم لإعادة النشاط اليومي والشفاء التام في وقت قصير بعد الكسر. هناك حاجة لمزيد من الدراسات لتأكيد هذه النتائج.